The Pólya-Szegö Principle and the Anisotropic Convex Lorentz-Sobolev Inequality - Shuai Liu; Binwu He (The Scientific World Journal)
An anisotropic convex Lorentz-Sobolev inequality is established, which extends Ludwig, Xiao, and Zhang’s result to any norm from Euclidean norm, and the geometric analogue of this inequality is given. In addition, it implies that the (anisotropic) Pólya-Szegö principle is shown.